Pengaruh Pemasaran pada Media Sosial dan Ulasan Pelanggan Online Terhadap Niat Beli Dimediasi oleh Kepercayaan Pelanggan: Studi Pada Pengikut Media Sosial Produk Kosmetik di Wilayah Jakarta - Vannisa Fahrani; Osly Usman; Shandy Aditya (Fakultas Ekonomi Universitas Negeri Jakarta, 2022)
The purpose of this research is to investigate the effect of social media marketing on customer trust, online customer review on customer trust, social media marketing on purchase intention, online customer review on purchase intention and customer trust on purchase intention of Scarlett Whitening's social media followers in the Jakarta area. The research data was collected by distributing questionnaires to Scarlett Whitening's social media followers and the sample of this study was 245 respondents. Researchers used Lisrel version 8.8 as a SEM application to process and analyze research data. The results of the study show a positive and significant influence between Social Media Marketing on Customer Trust, Online Customer Reviews have a significant effect on Customer Trust, Social Media Marketing has a significant effect on Purchase Intention, Online Customer Reviews have a significant influence on Purchase Intention, and Customer Trust has a significant effect on Purchase Intention to Scarlett Whitening online store. Tujuan dari penelitian ini adalah untuk melihat pengaruh social media marketing terhadap customer trust, online customer review terhadap customer trust, social media marketingterhadap purchase intention, online customer review terhadap purchase intention serta customer trust terhadap purchase intention pada pengikut sosial media Scarlett Whitening di wilayah Jakarta. Data penelitian dikumpulkan dengan penyebaran kuesioner kepada pengikut sosial media Scarlett Whitening dan sampel penelitian ini ialah sebanyak 245 responden. Peneliti menggunakan Lisrel versi 8.8 sebagai aplikasi SEM untuk mengolah dan menganalisis data penelitian. Hasil dari penelitian menunjukkan pengaruh positif dan signifikan antara Social Media Marketing terhadap Customer Trust, Online Customer Review berpengaruh signifikan terhadap Customer Trust, Social Media Marketing berpengaruh signifikan pada Purchase Intention, Online Review Customer memiliki pengaruh signifikan pada Purchase Intention, serta Customer Trust berpengaruh signifikan pada Purchase Intention terhadap toko online Scarlett Whitening.